SOCIAL-PHILOSOPHICAL ANALYSIS OF THE POSSIBILITIES OF ART IN THE PROCESS OF SPIRITUAL UPGRADE OF NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2025)
The article studies the theoretical foundations of the socio-philosophical analysis of the factor of art in the process of spiritual upliftment, the socio-philosophical aspects of the possibilities of art in the process of spiritual upliftment, the future tasks of the development of art in the process of spiritual upliftment. Also, the socio-philosophical analysis of the possibilities of art in the process of spiritual upliftment of New Uzbekistan is carried out.